Glocalização do McDonald's no Brasil: caso méqui - Noal, Nicolas Fiorot (Universidade do Vale do Rio dos Sinos, 2021)
Méqui, a name adopted by McDonald's in Brazil, was part of a campaign of glocal character, whose repercussion obtained remarkable relevance. The objective of this work, using the case study methodology, is to analyze the Méqui case and its impacts after changing the brand name to popular terms of Brazilian consumers. It is proposed to seek opinions, through qualitative and quantitative research to understand different audiences, in addition to bibliographic rescues to conceptualize the work. From the study conducted, it is understood the feasibility of replicating similar local campaigns in the country, but aware of the implications and risks.
Keywords: Marca; Marketing glocal; McDonald's; Brand; Glocal marketing